2017
DOI: 10.1186/s12961-017-0190-z
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of innovative and evidence-based practices for children and adolescents in state-supported mental health clinics: a qualitative study

Abstract: BackgroundThis study examined how mental health clinic administrators decided whether or not to adopt evidence-based and other innovative practices by exploring their views of implementation barriers and facilitators and operation of these views in assessment of implementation costs and benefits.MethodsSemi-structured interviews were conducted with 75 agency chief executive officers and program directors of 34 New York State-licensed mental health clinics serving children and adolescents.ResultsThree interconn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 24 publications
(26 reference statements)
1
36
0
1
Order By: Relevance
“…Transcripts were imported into ATLAS.ti (v 1.5.4, Scientific Software, Berlin, Germany). We used an inductive-deductive thematic analysis approach; an iterative process of coding to identify the patterns between concepts [29,30]. A team of three people, with experience in neonatology (A.L.)…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts were imported into ATLAS.ti (v 1.5.4, Scientific Software, Berlin, Germany). We used an inductive-deductive thematic analysis approach; an iterative process of coding to identify the patterns between concepts [29,30]. A team of three people, with experience in neonatology (A.L.)…”
Section: Discussionmentioning
confidence: 99%
“…Given the disappointing findings emerging from training studies and the recognition that context was important (McHugh & Barlow, ), implementation research entered a third wave, focused primarily on identifying determinants at multiple levels (e.g., clinician, organization, system) that might be related to implementation success or failure spurred on by the publication of several heuristic implementation frameworks (Aarons, Hurlburt, & Horwitz, ; Damschroder et al., ; Greenhalgh, Robert, Macfarlane, Bate, & Kyriakidou, ). Third wave studies often used mixed‐methods to describe the determinants or test the relationships between these determinants and a variety of implementation outcomes such as EBP adoption, fidelity, and sustainment (Beidas et al., , ; Locke et al., ; Palinkas et al., ; Stein, Celedonia, Kogan, Swartz, & Frank, ). We refer to this approach as the ‘ disaggregation paradigm’ because it involves dismantling established social science theories such as the Theory of Planned Behavior (Ajzen, ), Social Cognitive Theory (Bandura, ), Learning Theory (Blackman, ), and Organizational Climate Theory (Ehrhart, Schneider, & Macey, ) into their constituent variables (e.g., attitudes, organizational culture), measuring a large number of these variables in a single study, and examining which are most strongly associated with implementation in a single multivariate model that includes all measured variables.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the assessments of EBP implementation feasibility and desirability are based on different forms of engagement, including engagement with other EBPs at the Pre-Implementation phase and engagement with information or evidence, and with other stakeholders at the Pre-Implementation and Implementation phases. An earlier study by Palinkas et al ( 19 ) reported that personal experience was an important source of “evidence” used by systems leaders in deciding whether or not to implement EBPs. Clinical experience is one of the types of evidence used in the practice of evidence-based medicine ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…As Proctor et al ( 17 ), p. 72) have observed, “the success of efforts to implement evidence-based treatment may rest on their congruence with the preferences and priorities of those who shape, deliver, and participate in care.” Similar pragmatic arguments have been made by Bhattacharyya et al ( 18 ) who pose that theory is not necessarily better than “common sense” for guiding implementation. For example, highlighting the importance of fiscal viability and feasibility, a study by Palinkas et al ( 19 ) found that directors of youth-serving mental health clinics made decisions to adopt or not adopt innovative EBPs based on an assessment of costs and benefits associated with adoption, capacity for adoption, and acceptability of new practices. Moreover, assessment of costs and benefits exhibited several principles of behavioral economics including loss aversion, temporal discounting, use of heuristics, sensitivity to monetary incentives, decision fatigue, framing, and environmental influences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation